Global Trends of Animal Ethics and Scientific Research (Global Journal of Science Frontier Research, 2017)
This article deals with global trends and guidelines followed by different countries in scientific research. The various objectives of animal research, pros and con and alternative method for animal research by the use of 3Rs are disused here it is felt that however animal research is indispensible in several research but in certain alternative are alternately effective means of animal rights. This article reviews various aspects which are related to this issue.
Keywords: animal models; ethics; guideline; cons